Insights into the origin and evolution of carbonaceous aerosols in a mediterranean urban environment. (November 2019) - Galindo, N.; Yubero, E.; Clemente, A.; Nicolás, J.F.; Navarro-Selma, B.; Crespo, J.
Abstract: Organic carbon (OC) and elemental carbon (EC) concentrations were measured in PM1 and PM10 daily samples collected at an urban station in Elche (southeastern Spain) from February 2015 to February 2018. The effect of seasonal weather conditions, traffic, and specific pollution events (Saharan dust outbreaks and local pollution episodes) on the variability of carbonaceous aerosol levels was studied in this work. The joint contribution of carbonaceous species to PM1 and PM10 mass concentrations was, respectively, 48% and 26%. Both OC and EC concentrations were higher in winter than in summer because of the poor dispersion conditions and lower temperatures leading to the condensation of semivolatile species. Secondary organic carbon (SOC), estimated using the EC tracer method, also exhibited higher concentrations during winter, indicating that the prevailing meteorological conditions during the cold season are more favorable for the formation of secondary organic aerosols. Our results suggest different formation pathways of secondary organic components during summer and winter. At the sampling site, EC was primarily derived from traffic emissions, independently of the season and the type of event, with a modest contribution from biomass burning (<20%). The estimated contribution from this source to OC levels was similar. Local pollution episodes lead to a significant increase in the concentrations of carbonaceous species, in particular of SOC, influencing its temporal variation. On average, African dust outbreaks showed a moderate impact on the levels of carbonaceous aerosols; however, the effect was significantly stronger during winter Saharan events. Highlights: EC mainly emitted from traffic, with a minor influence of biomass burning. SOA production more affected by weather conditions than by photochemistry. Significant increases of carbonaceous species during local pollution events (LPE). Meteorological conditions during LPE especially suitable for SOA formation. Important increases of SOC levels during winter Saharan events.